Discovery and creation: alternative theories of entrepreneurial action - Alvarez, Sharon A.; Barney, Jay B. (Strategic Entrepreneurship Journal, 2007)
Abstract Do entrepreneurial opportunities exist, independent of the perceptions of entrepreneurs, just waiting to be discovered? Or, are these opportunities created by the actions of entrepreneurs? Two internally consistent theories of how entrepreneurial opportunities are formed – discovery theory and creation theory – are described. While it will always be possible to describe the formation of a particular opportunity as an example of a discovery or creation process, these two theories do have important implications for the effectiveness of a wide variety of entrepreneurial actions in different contexts. The implications of these theories for seven of these actions are described, along with a discussion of some of the broader theoretical implications of these two theories for the fields of entrepreneurship and strategic management. Copyright © 2007 Strategic Management Society.